Disclosure Narratives of Women Living with HIV in South Africa. (June 2017) - Iwelunmor, Juliet; Nwaozuru, Ucheoma; Sofolahan‐Oladeinde, Yewande; Conserve, Donaldson; Airhihenbuwa, Collins O.
Abstract : This study explored the disclosure narratives of women living with HIV (WLWH) to establish how they make sense of the stigmatized identity associated with HIV and decisions to conceal or reveal knowledge of their seropositive status to others. Forty‐eight WLWH participated in seven focus group discussions (with 42 participants) and six in‐depth interviews about their experiences with living with HIV and disclosure of their HIV seropositive status. The results suggest three key themes highlighting: (1) how HIV disrupted the identities of some of the participants, (2) how disclosure tested the strength of identities and relationships, and (3) how WLWH coped with HIV and disclosure. The findings help to reveal experiences that typically remain implicit or unrecognized as WLWH unite their past, with the present and a future identity, where HIV is moved from the foreground into the background.